2015
DOI: 10.1002/jcp.24981
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Factors Secreted by MSCs Promote Astrocyte Survival Associated With GFAP Downregulation After Ischemic Stroke via p38 MAPK and JNK

Abstract: Astrocytes are critical for ischemic stroke, and understanding their role in mesenchymal stem cell (MSC)-mediated protection against ischemic injury is important. The paracrine capacity of MSCs has been proposed as the principal mechanism contributing to the protection and repair of brain tissue. In the present study, an in vitro oxygen-glucose deprivation (OGD) model was used to mimic ischemic injury. OGD-induced astrocytes were reperfused with MSC-conditioned medium (MSC-CM) or co-cultured with MSCs for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 95 publications
2
43
0
Order By: Relevance
“…Certain positive results based on paracrine mechanisms have been reported in ischaemic stroke, myocardial infarction and kidney injury. 7 12 29 In the present study, the importance of paracrine effects was further supported by the observation of immediate protective effects within the first three days after transplantation, when hBMSC differentiation was far from complete. Furthermore, the paracrine effects of the implanted hBMSCs altered the recipient response to damage, from producing more apoptosis/cell death-related cytokines to producing more cytokines related to immunoregulation and developmental control, but the most altered cytokines were not produced by transplantation-derived cells.…”
Section: Discussionsupporting
confidence: 65%
“…Certain positive results based on paracrine mechanisms have been reported in ischaemic stroke, myocardial infarction and kidney injury. 7 12 29 In the present study, the importance of paracrine effects was further supported by the observation of immediate protective effects within the first three days after transplantation, when hBMSC differentiation was far from complete. Furthermore, the paracrine effects of the implanted hBMSCs altered the recipient response to damage, from producing more apoptosis/cell death-related cytokines to producing more cytokines related to immunoregulation and developmental control, but the most altered cytokines were not produced by transplantation-derived cells.…”
Section: Discussionsupporting
confidence: 65%
“…We speculate that most of the in vivo effects were achieved by paracrine effect, because we detected a substantial number of AMSCs in the lung, but not the rectum, after transplantation. Although the difference in characteristics among MSCs from different tissue is not thoroughly understood, one that OGD with MSC-CM could protect astrocytes from apoptosis, increase cell metabolic activity, and reduce overexpression of glial fibrillary acidic protein (GFAP) [39]. They suggested that paracrine factors inhibited p38 MAPK and JNK, most likely by regulating the downstream targets p53 and STAT1 to promote astrocyte survival associated with GFAP downregulation after ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSCs are capable of switching microglia from a proinflammatory M1 phenotype towards an anti-inflammatory M2 phenotype in vitro [13] and in SCI models [50]. Furthermore, MSCs inhibit reactive astrogliosis in inflammationinduced preterm brain injury [51], attenuate GFAP overexpression in astrocytes in stroke [52], and modulate astrocytic end-feet in lipopolysaccharide-treated rats [53]. However, little is known about the effect of MSCs on inflammatory A1 astrocytes after SCI.…”
Section: Discussionmentioning
confidence: 99%